BENTUK KOMPOSISI MUSIK GAMELAN DAN REFLEKSI TEOLOGIS ATAS “KU SUKA MENGABARKAN” - Alfa Kristanto; Denny Dwiatmadja Kristianto (Sekolah Tinggi Theologia Abdiel, 2018)
This article focuses on how Gereja Baptis Indonesia (GBI) Ngembak Semarang used Gamelan and a hymn they sang at worship on Sunday, 24th September 2017, namely Ku Suka Mengabarkan. Based on how GBI has been using Gamelan and by analyzing lyrics of Ku Suka Mengabarkan, this article shows that the Church does not only partake in preserving local Javanise traditional music but also nurture her members by singing hymns that their lyrics could affect their spirituality formating.